A micro deep drawing of ARB processed aluminium foil AA1235. (1st January 2013) - Hadi, Syamsul; Tieu, Anh Kiet; Lu, Cheng; Zhu, Hongtao
The flow stress of AA1235 aluminium series-H14 material of 16 to 300 μm thickness has been determined here for the first time which showed the stress reduced significantly with thickness. A stress-strain relationship has been determined as a function of the thickness and grain size. A limiting drawing ratio (LDR) of 2.003 was achieved by a subsequent heat treatment of accumulative roll bonded (ARB) materials before the micro-cup drawing. The cup was successfully formed as the combined process has reduced the planar anisotropy, increased the normal anisotropy and improved the formability of a cup.